Moment Capacity Charts for Strengthening of RC Beams With Near Surface Mounted FRP Reinforcement - Abdulkadir, Mohamad R.; MSc, Avin H. Abdullah (Sulaimani Journal for Pure and Applied Sciences, 2016)
Near surface- mounted fibre reinforced polymer is a new technique for strengthening structural members beside externally applied fibre reinforced polymer (FRP) technology. In NSM technique, the FRP material is applied to the tension region of the member inside pre-prepared grooves. In externally applied FRP the debonding of the fibres is a major issue thus, the full utilisation of FRP material can not be achieved, and the fibres are more susceptible to environmental effects. With NSM FRP, these issues can be controlled more effectively. ACI Committee 440 [1] has presented guidelines for design and construction of externally FRP method for strengthening of concrete structures. Although many experiments have been conducted on NSM FRP in flexure strengthening of RC beams, no code is introduced yet. Theoretical studies to derive equations for calculating moment capacity of strengthened beams have been introduced but mostly require several trial procedures to reach the required effective strain for FRP. In this study, a moment capacity chart is introduced based on several assumptions in the derivation of flexure capacity equation. To avoid the brittle behaviour of FRP, it is suggested that the utilization of FRP to be limited to 70% of its ultimate capacity for CFRP, and an equivalent area of reinforcement is adopted for simplicity. Experimental results of other researchers have been verified with the proposed charts, and a good comparison of results have being achieved.
Keywords: Beams,Nearsurfacemounted,fibre reinforcedpolymer,moment capacity